RUKHSHAH BAGI PENYANDANG DISABILITAS DALAM MENJALANKAN SYARIAT ISLAM PERSPEKTIF Q.S. AL-FATH: 17 - Ahzami, Hanifah; Purnamasari, Yulietta (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2021)
Persons with disabilities are still often underestimated by the wider community. Some parents even pay less attention to teaching religious knowledge, especially matters of worship, because they think that children with disabilities are not the same as children in general. Whereas God's purpose in creating humans on this earth is to worship Him. This problem needs to be studied to find the right and correct solution, so that parents realize that the main task that is very crucial is to guide children with disabilities to know Allah and teach Him how to worship Him according to His instructions. This paper uses qualitative research methods, dissects the verses of the Qur'an and examines the hadiths related to the relief given by Allah to persons with disabilities, as well as the opinion of the commentators on the interpretation of these verses, as well as explanations about the hadiths. the hadith of the Prophet . The result of this research is that Allah does not burden His people with something that is beyond their ability. Behind the difficulties in raising, caring for, accompanying, educating and nurturing children with disabilities, Allah gives them mercy in the form of rukhshah.